Paradigm of educational modernization Nurcholish Madjid perspective and relevance to the merdeka belajar concept - Abdurrohim; Sholeh, Mohammad; Zakki Fuad, Ahmad; Zaini, Achmad (ATTARBIYAH: Journal of Islamic Culture and Education, 2024)
The aim of this research is to analyze the development of Islamic education through the newly launched concept of "Merdeka Belajar" from the perspective of Nurcholish Madjid’s thoughts. This research employs a library research approach with in-depth descriptive analysis. The findings reveal that the achievements of educational reform in Indonesia through "Merdeka Belajar" have both relevance and gaps when compared to Nurcholish Madjid’s perspective on educational modernization in three areas: First, the relevance of the conception of values and development principles in the three dimensions of cognitive, affective, and psychomotor learning through a student-oriented learning approach. Second, the gaps in the practical implementation of "Merdeka Belajar," are: 1) the concept of "Merdeka Belajar" tends to be autonomous concerning the administration of education at educational units, creating opportunities for changes in educational direction; and 2) the aspect of educational equality, which remains uneven to this day. Therefore, these findings can serve as representative evaluation material for stakeholders and policymakers regarding the development of education in Indonesia, particularly in the context of Islamic education